K. U. Leuven Evaluation Centre: Leading the world in breaststroke research and its application (coachesinfo.com)
This paper provides background information for subsequent articles on breaststroke technique. In particular, the innovative `multi-media package`, used at K.U.Leuven Evaluation Centre of the Faculty of Kinesiology and Rehabilitation Sciences, to aid diagnosis and education in breaststroke swimming is introduced. In subsequent articles the team of researchers at K.U.Leuven Evaluation Centre will address important questions such as `Which style of breaststroke, e.g. flat or undulating, is best suited to particular physical characteristics such as strength, length, and flexibility?`, `What technique factors are important for undulating and flat breaststroke?`, `How can swimmers develop the necessary characteristics to improve technique in breaststroke?`.